Tongue Prints: A Forensic Review - Gargi Nimbulkar1 , Ruchita Patil2 , Simran Nathani2, Sakshi Salve2 , Kumar Gaurav Chhabra3 , Shravan (Institute of Medico-legal Publications Pvt Ltd, 2020)
Forensic odontology is a branch of forensic sciences which proof to be very helpful during investigationof criminal cases and during person identification by providing the dental expertise in the court and to thelegal system so that proper justice can be done based on evidence. The tongue is a crucial organ very muchencased inside the oral cavity and shielded from nature. Tongue print is the subtleties present on uncoveredsection of tongue when the surface and shape are assembled. The morphology and surface highlights areattributes of each person, and these characteristics can be utilized for criminological distinguishing proof.It has unique shape and surface textures in each individual. The shape, colour and texture of tongue aredifferent in identical twins. And hence it can be used as a new method for personal identification withfurther elaboration. The unique features make it a valuable tool in forensic odontology. The exposedportion of tongue contains information with visible differences from one individual to another therefore itis helpful in identification of suspect during forensic investigation. Tongue becomes the forensic evidencefor establishing the cause of death. It is an evolving science in the field of forensic and there is greater scopefor its further development. The use of tongue print as forensic identification is at budding stage but now itsuse as a biometric authentication system is gaining a lot of popularity. This review is aimed at describing thedistinctive features of tongue, application of tongue prints in personal identification and as biometric systemand the challenges faced in its use.